Engineered Nanoparticulate Vaccines to Combat Recurring and Pandemic Influenza Threats. Issue 3 (7th December 2021) - Dong, Chunhong; Wang, Bao-Zhong
Abstract : Recurring seasonal flu epidemics and occasional pandemics are among the most severe threats to public health. Current seasonal influenza vaccines provide limited protection against drifted circulating strains and no protection against influenza pandemics. Next‐generation influenza vaccines, designated as universal influenza vaccines, should be safe and affordable and elicit long‐lasting cross‐protective influenza immunity. Nanotechnology plays a critical role in the development of such novel vaccines. Engineered nanoparticles can incorporate multiple advantageous properties into the same nanoparticulate platforms to improve vaccine potency and breadth. These immunological properties include virus‐like biomimicry, high antigen loads, controlled antigen release, targeted delivery, and induction of innate signaling pathways. Many nanoparticle influenza vaccines have shown promising results in generating potent and broadly protective immune responses. This review summarizes the necessity and characteristics of next‐generation influenza vaccines and the immunological correlates of broad influenza immunity, and focuses on how cutting‐edge nanoparticle technology contributes to such vaccine development. The review gives new insights into the rational design of nanoparticle universal vaccines to combat influenza epidemics and pandemics. Abstract : Nanotechnology plays a critical role in the development of next‐generation universal influenza vaccines that produce long‐lasting cross‐protective influenza immunity. This review summarizes the necessity and characteristics of next‐generation influenza vaccines and the immunological correlates of broadly protective influenza immunity, emphasizing how cutting‐edge nanoparticle strategies contribute to the development of such vaccines to combat influenza epidemics and pandemics.